The grey king - Cooper, Susan; Cooper, Susan (United States of America: Cooper, Susan.)
In this volume of The Dark Is Rising sequence, Will Stanton, visiting in Wales, is swept into a desperate quest to find the golden harp and to awaken the ancient Sleepers.
The Golden Harp--The Oldest Hills--Cadfan's Way--The Raven Boy--Grey Fox--Fire on the Mountain--Birds Rock--Eyes That See The Wind--The Sleepers--The Girl from the Mountains--The Grey King--The Pleasant Lake--The Warestone--The Cottage on the Moor--The Waking
English